A pandemia de Covid- 19 e o impacto na saúde mental de docentes - Brito, Alane Renali Ramos Toscano de (2022)
Introduction: Covid-19, an infectious disease caused by the coronavirus (SARS-COV-2), was declared a pandemic in March 2020, entailed a series of changes in society's routine, which included restrictive measures to combat the spread of the virus. These changes had impacts on the population's mental health, especially for teachers, having to adapt to remote teaching in the home office mode, and this, depending on some characteristics, can become a sickening environment. Objective: To point out the impact on issues involving mental health that was affected by the Covid-19 pandemic on health teachers. Method: Descriptive study, with a secondary database, which involved 267 higher education professors in the health area. Data were processed by SPSS software version 26.0 and analyzed using descriptive statistics, with measures of central and inferential tendency, using Pearson's Chi-Square and Fisher's Exact Tests. Results: Dissatisfaction about mental health was more frequent among female teachers (49.3%), aged between 18 and 25 years (48.6%), divorced/separated (53.8%), with children (47.9%), with eating disorders (54.0%), who did not practice physical activity (53.4%), with an inadequate sleep pattern (65.6%) and using psychotropic medication (58, 7%). With regard to aspects of life, those with interference in the emotional (58.4%), spiritual (58.7%), financial (52.3%), physical (50.7%) and sexual (70. 4%) were also relevant about poor mental health. Of the mentioned variables, there was statistical significance for food (p=0.015), sleep pattern (p<0.001), and emotional and sexual aspects (p<0.001). Conclusions: It is hoped that this study can contribute to the adoption of measures that minimize the impacts generated by Covid-19 on the mental health of teachers, with the creation of effective strategies aimed at raising awareness and training of professionals who make up the teaching environment higher.